G435(P) Paediatric trainees: training and supporting the next generation of consultants. (May 2019) - Eyton-Chong, CK; Southward, S; Halfhide, C
Abstract : Aims: A large mixed secondary and tertiary children's hospital faced a shortfall in trainee allocations resulting in multiple rota gaps. A recent move to a new site challenged the pre-existing on-call arrangements for the medical team. Concerns for patient safety prompted a survey to review and improve the out of hours working dynamics for the on-call team. Methods: Trainees were asked to complete a survey after their on calls. Results were collated and fed-back to the hospital 'Out of Hours' working group. Changes were implemented and the survey repeated to assess the effects. The initial survey was conducted April to June 2017 and repeated between November to January 2018. Results and discussion : During the initial survey a third of shifts were short staffed whilst all shifts were filled during the second survey. Despite shortages trainees reported they were able to prioritise their sick patients 86% of the time and well supported by on call consultants 84% of time. During the second survey this was 83% and 90% respectively. Analysis of results revealed that when consultants filled the gaps in the rota that trainees felt safer and better supported. In the repeat survey, the workload was felt to be manageable in only 70% of the shifts. In order to help lighten the workload, a third registrar was initially introduced on the weekends and subsequently across the whole week. During both surveys 30% of shifts had unexpected admissions to critical care suggesting that the work intensity was comparable during both time periods. Conclusion: Increased numbers on the call rota eases the workload but may not directly impact on that perceived safety of patient care. As expected, resident consultants support decision making and patient safety. Currently we do not have formal 7 day working for subspecialties. Increasing consultant presence outside of office hours helps to improve both patient safety and patient flow. 1, 2 As trainee numbers decline, many future rotas will involve a hybrid with advanced nurse practitioners as well as consultants working extended hours or resident shifts. 2 References: https://improvement.nhs.uk/documents/1426/Patient_Flow_Guidance_2017___13_July_2017.pdf https://www.rcpch.ac.uk/sites/default/files/CDC_full_report_24_04_12_V2.pdf